2021
DOI: 10.3389/fphar.2021.771487
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine-Induced Peripheral Neuropathy in Childhood Acute Lymphoblastic Leukemia: Genetic Variation as a Potential Risk Factor

Abstract: Vincristine (VCR) is the first-line chemotherapeutic medication often co-administered with other drugs to treat childhood acute lymphoblastic leukemia. Dose-dependent neurotoxicity is the main factor restricting VCR’s clinical application. VCR-induced peripheral neuropathy (VIPN) sometimes results in dose reduction or omission, leading to clinical complications or affecting the patient’s quality of life. With regard to the genetic basis of drug responses, preemptive pharmacogenomic testing and simultaneous blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 146 publications
2
12
0
Order By: Relevance
“…Disparate results currently exist as to whether fluconazole increases the rates of vincristine-associated neuropathy. However, older age has been identified by some studies as a risk factor for the development of neuropathy in patients receiving both vincristine and fluconazole 17,18 . The results of our study add to the growing body of literature supporting the idea that advanced age does increase the risk of developing vincristine-induced peripheral neuropathy (VIPN).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Disparate results currently exist as to whether fluconazole increases the rates of vincristine-associated neuropathy. However, older age has been identified by some studies as a risk factor for the development of neuropathy in patients receiving both vincristine and fluconazole 17,18 . The results of our study add to the growing body of literature supporting the idea that advanced age does increase the risk of developing vincristine-induced peripheral neuropathy (VIPN).…”
Section: Discussionsupporting
confidence: 55%
“…The 2011 cohort study by Schie et al 16 found increased neurotoxicity with vincristine and azole coadministration; however, the majority of subjects received itraconazole with only 1 subject receiving fluconazole. As fluconazole is a weaker, noncompetitive inhibitor of several human CYP proteins and does not significantly inhibit P-gp as compared with itraconazole or posaconazole, there seem to be fewer adverse drug reactions between it and vincristine 4,17 . Disparate results currently exist as to whether fluconazole increases the rates of vincristine-associated neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in 2020, an investigation among 150 pediatric patients with ALL and Wilm’s tumors showed that significant side effects of the vincristine regimen are mostly neurotoxic, which is at a mild to moderate level [ 65 ]. In recent years, more and more studies have revealed the deep connection between genetic polymorphisms and VIPN [ 66 , 67 , 68 ]. The CEP72 genetic variant is an optimistic VIPN signature marker since the CEP72 gene encodes centrosome proteins that participate in the development of microtubules.…”
Section: Severe Neuropathy and Myopathy Side Effects In Chemotherapymentioning
confidence: 99%
“…Patients with preB ALL who expressed CYP3A5 showed less vincristine-induced peripheral neuropathy (VIPN), generated more M1, and had lower metabolic rates than those who did not express CYP3A5 [ 32 ]. The CEP72 gene genetic variations have a lot of therapeutic potential [ 33 ]. Another genetic variant possibly related to the vincristine response is lower NHP2L1 mRNA expression in leukemia cells derived from children with recently diagnosed ALL, which was substantially related to enhanced sensitivity to VCR in B- and T-cell leukemia [ 34 ].…”
Section: Neurotoxicity Of Conventional Therapymentioning
confidence: 99%